Risk of Corneal Inflammatory Events with Silicone Hydrogel and Low Dk Hydrogel Extended Contact Lens Wear: A Meta-Analysis - Loretta Szczotka‐Flynn; Mireya Díaz (2007)
High Dk silicone hydrogel (SH) lenses have been shown to significantly decrease the risk of hypoxic complications compared to traditional low Dk hydrogels. However, the risks of inflammatory complications with SH compared to low Dk lenses are not as clear. A meta-analysis was performed to combine the relevant literature to evaluate the risks of corneal inflammatory events in users of SH and low Dk hydrogel extended wear lenses.A systematic search was conducted using online databases, unpublished meeting abstracts, and retrieval of other cited references presented or published between 1990 and February 2006. Each study was evaluated for quality in terms of the research question, and these quality assessments were used to determine which studies should be used in subgroup analyses. A generalized linear mixed model framework with an underlying Poisson distribution for the occurrence of events was employed to combine information from the included studies.Twenty-three studies published or presented on either or both arms by February 2006 were selected for analysis. A total of 9,336 subjects and 18,537 eyes comprised the entire sample. Seven studies were published in the 1990s. Eighteen studies (78%) were prospective, and 11 (48%) used randomization. The follow-up ranged from 4 to 36 months, with a median of 12 months. The rates of infiltrates for low Dk hydrogels and SH lenses were 7.7 (2.2, 26.7) and 14.4 (4.3, 48.2) per 100 eye-years, respectively. In the subset of five best quality studies, the unadjusted risk ratio for corneal inflammatory events for SH lenses compared to low Dk lenses was 2.18 (p < 0.005). Across studies, adjusted risk ratios ranged from 2.18 to 2.23 (p < 0.05), with strong confounding between material and length of wear.Based on published or presented studies between 1991 and 2006, there is approximately a twofold higher risk for corneal inflammatory events in users of SH lenses when typically worn for up to 30 days extended wear when compared with low Dk extended wear lenses when typically worn for 7 days extended wear. The increased risk cannot be definitively linked to SH lens materials because the effect of material on outcome is confounded by length of wear.